Research status of behaviour decision-making for intelligent vehicles. (10th September 2019) - Tan, Di; Liu, Shuaishuai; Li, Ruixian; Yang, Kun
Intelligent vehicles will gradually replace human driving with the intelligence of intelligent vehicles continuing to increase, which is one of the necessary ways to solve the traffic accidents and traffic congestion caused by incorrect driving of humans. The behaviour decision-making system is the core part of intelligent vehicles. This system determines whether intelligent vehicles can produce driving behaviour of reason, and plays a vital role in the safety of intelligent vehicles. The research status of behaviour decision-making methods of intelligent vehicles and the different behaviour decision-making methods used in different scenarios are summarised by this paper. The difficulties in behaviour decision-making of intelligent vehicles are summarised and the future development direction of decision-making is discussed.